Cholesterol-linked beta-cyclodextrin - a thermotropic liquid-crystalline derivative - Shaikh, Vasi Ahmed Ebrahim; Lonikar, Shrikant Vitthal; Dhoble, Deepa Arun; Pawar, G. M. (Bulletin of the Chemical Society of Japan, 2007)
Liquid-crystalline derivative of ss-cyclodextrin (BCD) was prepared by covalent linking of monocholesteryl succinate (ChMS) with ss-cyclodextrin. To the best of our knowledge, this was first ever attempt so far of its kind, in which BCD has been converted into its liquid-crystalline derivative through covalent linkage of a mesogen. The degree of substitution (DS) obtained was approximate to 2.00. The product was characterized by various techniques, such as FT-IR, NMR, DSC, hot-stage-coupled optical polarizing microscopy (OPM), microanalysis and chemical methods. Cholesterol-linked ss-cyclodextrin (CDCh) derivative was found to exhibit thermotropic liquid-crystalline behavior. The product exhibited birefringence during first heating above 130 degrees C, and it became isotropic at about 180 degrees C, whereas the parent compound BCD decomposed without melting above 250 degrees C. A comparison of CDCh derivative to similar liquid-crystalline polysaccharide derivatives is presented.

Controlled synthesis of low-molecular-weight polyethylene waxes by titanium-biphenolate-ethylaluminum sesquichloride based catalyst systems - Umare, Prashant S.; Rao, Karumanchi; Tembe, Gopal L.; Dhoble, Deepa Arun; Trivedi, Bhavna (Journal of Applied Polymer Science, 2007)
Soluble complexes of titanium(IV) bearing sterically hindered biphenols, such as biphenol, 1,1'-methylene di-2-naphthol, 2,2'-methylene bis(4-chlorophenol), 2,2'-methylene bis(6-tert-butyl-4-ethyl phenol), and 2,2' ethylidene bis(4,6-di-tert-butyl phenol), were prepared and characterized. These catalyst precursors, formulated as [Ti((OO)-O-boolean AND)X-2], were active in the polymerization of ethylene at high temperatures in combination with ethylaluminum sesquichloride as a cocatalyst. The ultra-low-molecular-weight polyethylenes (PEs) were linear and crystalline and displayed narrow polydispersities. The catalytic polymerization leading to PE waxes in this reaction exhibited unique properties that have potential applications in surface coatings and adhesive formulations. (c) 2007 Wiley Periodicals, Inc.
Keywords: Catalysts; polyethylene (PE); synthesis; Ziegler-Natta polymerization

Polyethylene waxes: catalytic synthesis by ti-biphenolates - Umare, Prashant S.; Rao, Karumanchi; Tembe, Gopal L.; Dhoble, Deepa Arun; Trivedi, Bhavna (Journal of Macromolecular Science Part A‐Pure and Applied Chemistry, 2007)
{Soluble complexes of Ti (IV) bearing biphenol groups such as 1,1'-binaphthelene 2, 2' diol (Binol), 1, 1'-methylene di-2-naphthol, biphenol were prepared and characterized. These catalyst precursors formulated as [
Keywords: fibers; Nanoparticles; Self-assembly

Amino functionalized oligoimides telechelics - Dwivedi, Mayank; Rao, Locanindi Hari Sarvothama; Reddy, Krishna Mohan Srinivasulu; Dhanasekharan, Janakiraman; Rao, Bevara Madhusudana; Kumar, Sriperambudur Rajesh; Ponrathnam, Surendra; Rajan, Chelanattukizhakkemadath Raman; Deokar, Sarika Babasaheb; Mulani, Khudbudin Baban; Ghorpade, Ravindra V.; Bhongale, Sunil Sitaram; et al. (2010)
This invention relates to a process for the preparation of amino functionalized oligoimide telechelics. More particularly it relates to a process for the preparation of soluble oligoimide prepolymers which can be used as matrix resins that can be rapidly cured to form stable polyimides with amino end functionalities. The amino functionalized oligoimide telechelics are suitable for conversion into three dimensional polymeric systems through condensation chemistry such as reaction with oligo epoxies (epoxy-imide resins), polyacids (polyamide imides) and polyhalogenated compounds (poly amine - imides) to form crosslinked structures having enhanced thermal stability and mechanical strength. The polymers prepared by the process of this invention can be used as materials in advanced composites having high temperature stability.

Amino functionalized oligo polyimides with enhanced storage stability - Dwivedi, Mayank; Rao, Locanindi Hari Sarvothama; Mohan, Srinivasulu Reddy Krishna; Dhanasekharan, Janakiraman; Rao, Bevara Madhusudana; Kumar, Sriperambudur Rajesh; Ponrathnam, Surendra; Rajan, Chelanattukizhakkemadath Raman; Tayal, Rajiv Kumar; Shadbar, Qureshi Mohammed; Chavan, Nayaku; Deokar, Sarika Babasaheb; et al. (WO2012090055A1, 2012)
The invention relates to an improved process for the preparation of amino functionalized oligomeric monomeric reactant type polyimides having higher stability. More particularly it relates to a process for the preparation of soluble imide prepolymers, used as matrix resins that can be rapidly cured with multi-functional moieties such as diepoxy, dicarboxyl, anhydride, diisocyanates to form crosslinked structures having enhanced thermal stability and mechanical strength.

Ethyl oligo-silicates with strong acid heterogeneous polymeric catalysts - Bevara, Madhusudana Rao; Bhongale, Sunil Sitaram; Bhosle, Sonali Madhavrao; Chavan, Nayaku; Chelanattukizhakkemadath, Raman Rajan; Deokar, Sarika Babasaheb; Dhoble, Deepa Arun; Dwivedi, Mayank; Ghorpade, Ravindra V.; Harikrishna, Reghunathan; Dhanasekharan, Janakiraman; John, Aruldoss; et al. (WO2012056290 A1, 2012)
The present invention provides a process for the synthesis of ethyl silicate with varying silica concentration, by hydrolysing ethyl silicate in varying water concentration in the presence of sulfonated catalysts having a styrene-divinyl benzene backbone. The present invention further relates to the preparation of beaded crosslinked polymers containing sulfonic acid moieties having an interconnected pore structure and surface area up to 400 m2 /g.

Long chain branched impact copolymer of polypropylene: microstructure and rheology - Chikhalikar, Kalyani; Deshpande, Anushree; Pol, Harshawardhan; Dhoble, Deepa Arun; Jha, Saroj; Jadhav, Kishor; Mahajan, Sunil; Ahmad, Zubair; Kulkarni, Surendra; Gupta, Surendra; Lele, Ashish K. (Polymer Engineering and Science, 2015)
A biphasic impact copolymer of polypropylene (ICP) was modified with peroxide by reactive extrusion process resulting in reduced melt flow index, improved melt strength, and higher die swell. The polymers were for the first time subjected to systematic rheological and microstructural characterization in an effort to understand their structure-property relations. In shear rheological tests, the modified ICP displayed higher flow activation energy, reduced values of loss tangent and nearly equal frequency dependence of storage and loss modulli. The modified ICP also showed strain hardening behaviour in uniaxial extensional rheology and higher crystallization temperature in differential scanning calorimetry (DSC). All these are definitive indications of the presence of long chain branches (LCB). Fitting the rheological data of modified ICPs with the eXtended Pom Pom (XPP) model indicated the presence of LCB on the higher molecular weight fraction in the polymer, a result which was corroborated with multi-detector high temperature gel permeation chromatography (HT-GPC). More importantly, the matrix and rubber phases of the ICP were separately characterized for presence of long chain branching by rheology, DSC and HT-GPC. The results indicate that while LCB existed in the matrix phase, microgels were present in both phases indicating that the reaction with peroxide occurred in both phases. POLYM. ENG. SCI., 55:1463-1474, 2015. (c) 2014 Society of Plastics Engineers

Proton play in the formation of low molecular weight chitosan (LWCS) by hydrolyzing chitosan with a carbon based solid acid - Krishnan, R. Akhil; Deshmukh, Pranjal; Agarwal, Siddharth; Purohit, Poorvi; Dhoble, Deepa Arun; Waske, Prashant; Khandekar, Dileep; Jain, Ratnesh; Dandekar, Prajakta (Carbohydrate Polymers, 2016)
Low molecular weight chitosan (LWCS) constitute a special class of value added chemicals that are primarily obtained from crustacean shells, which are the main water pollutants from crabs and shrimp processing centers. Unlike chitin and chitosan, LWCS possess improved solubility in water and aqueous solutions, making them widely applicable in numerous fields ranging from drug delivery to waste water treatment. Among the methods employed for their production, chemical breakdown by strong liquid acids has yielded good success. However, this method is met with severe concerns arising from the harsh nature of liquid acids, which may corrode the reactors for commercial synthesis, and their limited reusability. The physical methods like ultrasound and microwave are energy intensive in nature, while the enzymatic methods are expensive and offers limited scope for reuse. We have attempted to overcome these problems by employing carbon based solid acid (CSA) for hydrolyzing chitosan to LWCS. CSA can be easily produced using activated carbon, a cost-effective and easily available raw material. Reactions were carried out between chitosan and CSA in a hydrothermal glass reactor and the products, separated by cold centrifugation, were purified and dried. The dried products were characterized for their molecular weight and solubility. Results indicated more than ten-fold decrease in the molecular weight of chitosan and the product exhibited water solubility. The CSA could be used upto four times, without regeneration, to give a consistent quality product. The aqueous solution of resulting LWCS exhibited a pH of 6.03 +/- 0.11, as against the acidic pH range of solutions of commercially available LWCS, indicating its suitability for biomedical applications. Our investigation facilitates a `green approach' that may be employed for commercial production of value added chemicals from waste products of marine industry. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Carbon based solid acid; Chitosan; green synthesis; Hydrolysis; Low molecular weight chitosan